Zoonotic Babesia microti in the northeastern U.S.: Evidence for the expansion of a specific parasite lineage - Goethert, Heidi K. (PLoS One, 2018)
The recent range expansion of human babesiosis in the northeastern United States, once found only in restricted coastal sites, is not well understood. This study sought to utilize a large number of samples to examine the population structure of the parasites on a fine scale to provide insights into the mode of emergence across the region. 228 B. microti samples collected in endemic northeastern U.S. sites were genotyped using published Variable number tandem repeat (VNTR) markers. The genetic diversity and population structure were analysed on a geographic scale using Phyloviz and TESS, programs that utilize two different methods to identify population membership without predefined population data. Three distinct populations were detected in northeastern US, each dominated by a single ancestral type. In contrast to the limited range of the Nantucket and Cape Cod populations, the mainland population dominated from New Jersey eastward to Boston. Ancestral populations of B. microti were sufficiently isolated to differentiate into distinct populations. Despite this, a single population was detected across a large geographic area of the northeast that historically had at least 3 distinct foci of transmission, central New Jersey, Long Island and southeastern Connecticut. We conclude that a single B. microti genotype has expanded across the northeastern U.S. The biological attributes associated with this parasite genotype that have contributed to such a selective sweep remain to be identified.